High indium non-polar InGaN clusters with infrared sensitivity grown by PAMBE - Shruti Mukundan; Lokesh Mohan; Greeshma Chandan; Basanta Roul; S. B. Krupanidhi; Satish Shinde; K. K. Nanda; R. Maiti; S. K. Ray (AIP Advances, 2015)
Studies on the optical properties of InGaN alloy of relatively higher indium content are of potential interest to understand the effect of indium content on the optical band gap of epitaxial InGaN. We report the growth of self assembled non-polar high indium clusters of In0.55Ga0.45N over non-polar (11-20) a-plane In0.17Ga0.83N epilayer grown on a-plane (11-20)GaN/(1-102) r-plane sapphire substrate using plasma assisted molecular beam epitaxy (PAMBE). Such structures are potential candidates for high brightness LEDs emitting in longer wavelengths. The high resolution X-ray diffraction studies revealed the formation of two distinct compositions of InxGa1−xN alloys, which were further confirmed by photoluminescence studies. A possible mechanism for the formation of such structure was postulated which was supported with the results obtained by energy dispersive X-ray analysis. The structure hence grown when investigated for photo-detecting properties, showed sensitivity to both infrared and ultraviolet radiations due to the different composition of InGaN region.